Adaptive Non‐Linear Control of UPFC for Stability Enhancement in a Multimachine Power System Operating with a DFIG Based Wind Farm. Issue 4 (6th February 2017) - Routray, S.K.; Patnaik, R.K.; Dash, P.K.
Abstract: An instantaneous converter power based adaptive second order sliding mode control for the Unified Power Flow Controller (UPFC) in a multimachine power system penetrated with a doubly fed induction generator (DFIG) based wind farm is proposed in this paper. Instead of controlling the direct and quadrature‐axis currents of the series voltage source converter (VSC) of the UPFC, the instantaneous active and reactive power outputs are used as control variables. This mode of control dispenses the unmodelled dynamics of the VSC phase‐locked loop (PLL) system and produces a robust control for the active–reactive power, and DC voltage excursions. However, the PLL is used only to obtain the frequency component needed to generate the Pulse Width Modulation (PWM) signal. In comparison to the first order sliding surface, the second order sliding surface provides very good robustness features, finite reaching time, and chattering free sliding mode behavior. Further, the proposed controller gains of the UPFC are chosen in accordance with the various constraints imposed by the second order sliding mode approach to provide significantly superior and robust performance for a number of diverse operating conditions of the network in comparison to the conventional sliding mode controller.